Proceedings of the 17th ACM Conference on Information and Knowledge Management 2008
DOI: 10.1145/1458082.1458251
|View full text |Cite
|
Sign up to set email alerts
|

A system for finding biological entities that satisfy certain conditions from texts

Abstract: Finding biological entities (such as genes or proteins) that satisfy certain conditions from texts is an important and challenging task in biomedical information retrieval and text mining. It is essential for many biomedical applications, such as drug discovery which normally requires collecting existing scientific facts from documents. This paper presents an effective IR system for this task, in which 1) domain knowledge is incorporated to improve retrieval effectiveness; 2) query expansion with related conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Recently, researchers in biomedical information retrieval and question answering continue to leverage the TREC Genomics data set for evaluation [37,14,32,20,23,17,5]. Given the absence of an easy-to-use framework for building baseline systems for new tasks and exploring large parts of the configuration space, iterative research typically focuses on perturbations to a single module while keeping modules and parameters elsewhere in the system frozen.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, researchers in biomedical information retrieval and question answering continue to leverage the TREC Genomics data set for evaluation [37,14,32,20,23,17,5]. Given the absence of an easy-to-use framework for building baseline systems for new tasks and exploring large parts of the configuration space, iterative research typically focuses on perturbations to a single module while keeping modules and parameters elsewhere in the system frozen.…”
Section: Related Workmentioning
confidence: 99%
“…However, they reported that their approach was insufficient to deal with the ambiguity of acronyms. Similarly, Zhou et al [6] used the ADAM acronym database to expand long-forms in the query with the corresponding acronyms as query concepts for their conceptbased retrieval framework. Still, they encountered problems with the ambiguity of acronyms and gene names.…”
Section: Introductionmentioning
confidence: 99%